1982
DOI: 10.1139/b82-170
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of cellular amino acids, protein, and total organic nitrogen during fruit body development in Flammulina velutipes. II. Growth on potato–glucose solution

Abstract: et W. M. WONG. 1982. Distribution of cellular amino acids, protein, and total organic nitrogen during fruitbody development in Flammulina velutipes. 11. Growth on potato-glucose solution. Can. J. Bot. GRUEN, H. E., and W. M. WONG. 1982. Distribution of cellular amino acids, protein, and total organic nitrogen during fruitbody development in Flammulina velutipes. 11. Growth on potato-glucose solution. Can. J. Bot. 60: 1342-1351.In Flammulina velutipes grown on potato-glucose solution the dry weight of mycelium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 3 publications
0
12
0
Order By: Relevance
“…Earlier studies (Gruen andWang, 1982, Zakhary et al, 1993) indicate that mushrooms are highly nutritious and compare favorably with meat, egg and milk. In the terms of amount of crude protein, mushrooms are ranked well above cereals/vegetables or fruits and animal products but below most meats (Chang and miles, 1989).…”
Section: Introductionmentioning
confidence: 96%
“…Earlier studies (Gruen andWang, 1982, Zakhary et al, 1993) indicate that mushrooms are highly nutritious and compare favorably with meat, egg and milk. In the terms of amount of crude protein, mushrooms are ranked well above cereals/vegetables or fruits and animal products but below most meats (Chang and miles, 1989).…”
Section: Introductionmentioning
confidence: 96%
“…The high proteins and trace minerals concentration is the main reason for the significant increase of wild edible mushrooms consumption (Ogundana and Fagade, 1982, Senatore, 1990, Thimmel and Kluthe,1998. Many researches revealed that the amino acid intake through the compositions of mushrooms are comparable to animal proteins (Fink and Hoppenhause, 1958;Gruen and Wong, 1982), which has great importance due to the fact that human nutrition has become more complex since the appearance of several diseases affecting animal meat production. However, it is evident that the step by step substitution of meat with mushroom will involve a very detailed assessment of chemical and biological properties.…”
Section: Introductionmentioning
confidence: 99%
“…The consumption of wild edible mushrooms is increasing due to a good content of proteins and trace minerals (Ogundana & Fagade, 1982;Senatore, 1990;Thimmel & Kluthe, 1998). Some investigations have even contended that the amino acid compositions of mushrooms are comparable to animal proteins (Fink & Hoppenhaus, 1958;Gruen & Wong, 1982), which is particularly important considering that human nutrition has become more complicated since the outbreak of diseases connected with animal meat. Although, the nutritional potential or implications of this gradual replacement of meat with mushroom requires careful examination which involves detailed chemical and biological studies.…”
Section: Introductionmentioning
confidence: 99%